PENGARUH MOTIVASI, KOMPENSASI, DAN LINGKUNGAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN DI KANTOR DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KOTA YOGYAKARTA - Badriyah Badriyah; Ani Muttaqiyathun (Jurnal Fokus Manajemen Bisnis, 2015)
This  research  aims  to  understand  how  the  influence  of  motivation, compensation  and workplace on the performance of employees at department office social  man power  and  transmigration the city of Yogyakarta bot  a partial as well as simultaneous or together. The population on this research is Employees who worked at social department office of  manpower and transmigration city of Yogyakarta. The sample collection  technique  in  this  research  use  of  sampling  methods  purposive. The total sample taken in this research as many  81 respondents. The source of data from the study  used  data  primary  obtained  from  the  results  of  questionnaires  compiled  using likert scale. This study using data analysis techniques is the quantitative analysis (linear regression analysis double, t test and test f). Test results t show that the significance of the variables ( x1 ) 0,007 value <  α = 0.05, then motivation influential significantly to employee performance, then motivation influential significantly to employee performance, variable compensation ( x2 ) 0,038 < value  α  =  0.05  then compensation significant of the performance of  employees and variable workplace (x3) 0,048  <  value α = 0.05 and a significant effect on the employees in social department office of manpower and transmigration the city of Yogyakarta.